Estudo experimental de válvulas de extintores de incêndio e seus aspectos legais - Amaral, Danilo (1995)
Fire extinguisher are safety equipments that are present daily in the major part of our lifes, meanly in the workplace and the vehicles, where their use is obliged by law. This work presents an experimental study of a valve P1/P2 which equip the fire extinguisher of motor vehicles. An analysis about the legal aspects that involves the technical responsabilities of the project, manufactoring, assembly line, operation and maintence. The compatibility between the technology with their technical rules, the Iegislation that define responsability over products and the insurance that cover the damages, increase as a tendence of the organized society in order to improve the profissionais job related with the criation, manufactoring and distribuition of the products. This tendence goes on the direction of a major security and quality of products which threat the life and the patrimony, mainly when the product is a equpment essential to avoid and fíght fires. This experimental study report the results of the destructive tests, micro-hardness, dimensional and Chemical composition of the material which the valve is manufactored, as well as the three dimensional photoelasticity analysis to obtain the stresses in the criticai points and the factors of safety adopted. An different lay-out for the inside thread of the valve is compared whith the actual design. Finally, a particular damage valve that has fractured accidentally is also analysed to identify the causes of the failure, based on the obtained results.